Small winch tractor - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A Zimbabwian designer has been testing a two-wheeled winch tractor on small farms for the last few years, with encouraging results. Small farmers in tropical regions with distinct dry and rainy seasons often experience great difficulty in field...